A Study on The Impact of Unplanned Pregnancy on Maternal Mental Health - Rajlakshmi M, Rajlakshmi M; Nirupa, Nirupa; Washington, Jasmine Kavitha; Washington, Washington (Journal of Neonatal Surgery, 2025)
Unplanned pregnancy can significantly affect a woman's psychological well-being, particularly during the antenatal period. This cross-sectional study was conducted at Sree Balaji Medical College and Hospital to assess the impact of unplanned pregnancy on maternal mental health, with a focus on anxiety levels. A total of 56 pregnant women aged 18 years and above with self-reported unplanned pregnancies were recruited using purposive sampling. Data were collected using a structured questionnaire that included socio-demographic and obstetric details, pregnancy acceptance, and the Generalized Anxiety Disorder-7 (GAD-7) scale. Statistical analysis revealed that younger age, lower education level, non-healthcare occupation, low socio economic status, and poor pregnancy acceptance were significantly associated with higher anxiety levels (p < 0.05). The findings underscore the need for routine mental health screening and emotional support interventions in antenatal care, especially for women with unplanned pregnancies, to promote maternal well-being and improve pregnancy outcomes.